Effectiveness of Participatory, Innovative, Collaborative Training Management in Improving Midwives' Competency - Mei Yati Simatupang; Syawal Gultom; Arif Rahman (Universitas Negeri Surabaya, 2026)
Midwives’ competence plays a vital role in improving maternal and child health services, particularly in stunting prevention. However, many midwives still do not meet the required competency standards. This study aimed to evaluate the effectiveness of Participatory, Innovative, and Collaborative (PILAR)-based training in enhancing midwives’ competence in West Nias Regency. Using a quasi-experimental design, 52 midwives were divided equally into an intervention group that received PILAR-based training and a control group without training. Independent t-test results indicated that the PILAR-based training management was effective in improving midwives’ competence (p = 0.001). These findings suggest that participatory, innovative, and collaborative approaches in training can strengthen midwives’ professional competencies and improve the quality of maternal and child health services. The study implies that integrating PILAR-based training into continuous professional development programs can serve as a strategic model for reducing stunting and promoting sustainable health outcomes in rural areas.